Influencing Factors in OER Usage of Adult Learners in Korea - Kim, Byoung Wook; Lee, Won Gyu; Lee, Byeong Rae; Shon, Jin Gon (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
Open Educational Resources (OER) is terminology that refers to educational resources (content and software) distributed through the Internet, free of charge and freely accessible, expanding learning opportunities for adult learners. This terminology first appeared around 2002, although its roots can be traced to the open architecture of the Internet. Until recently, OER development has focused more on quantity of contents rather than quality. In this study, we have examined the factors influencing the learning intention of adult learners in the OER context. Based on the relevant literature, we have identified a number of factors influencing a learner’s intention to use e-learning content. We have also developed a questionnaire for conducting a survey on such influencing factors. The survey results show that ease of use and relation to immediate workplace needs affect the intention of adult learners in using OER. The findings of this study can inform those developing and designing a learning environment that employs OER while also providing general guidance for developers and educators on how to design OER content.